Peran literasi digital islami dalam meningkatkan kemandirian belajar peserta didik pada mata pelajaran pendidikan agama islam - Sabrina, Noorma Faza (Maliki Interdisciplinary Journal, 2026)
The rapid growth of digital technology has made students increasingly attached to gadgets and social media. Without digital skills grounded in Islamic values, however, internet use can lead to religious misunderstanding and reduced learning focus. This article explores the role of Islamic digital literacy in strengthening students’ self-directed learning in Islamic Education (PAI) classes. Using a library research approach, it reviews books, journal articles, and academic works on digital literacy, Islamic Education, and self-regulated learning, including publications by lecturers of UIN Maulana Malik Ibrahim Malang. The findings indicate that Islamic digital literacy: helps students access reliable Islamic learning resources, enhances critical thinking and verification of online religious information, supports planning and managing PAI learning through digital platforms, and fosters responsible and ethical media use. Therefore, integrating Islamic digital literacy into Islamic Education is essential to promote students’ learning autonomy in line with the aims of Islamic education.